TIPS DAN TRIK PENULISAN JURNAL DAN PUBLIKASI TERINDEKS SQOPUS Q2 - Masriah Masriah; B. Hermawan Hayadi; Aisyah Aisyah; Indah Melati; Masruroh Masruroh (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
Publishing in Scopus Q2 indexed journals requires a comprehensive understanding of academic writing standards, research quality, and strategic publication planning. This study presents a structured overview of effective tips and practical strategies to support researchers in achieving successful publication outcomes. The process begins with identifying a significant research problem and establishing a clear research gap, which serves as the foundation for developing novelty and scientific contribution. A well-organized manuscript following the IMRAD structure—comprising Introduction, Methods, Results, and Discussion—is essential to ensure logical coherence and clarity. In addition, the use of appropriate academic language plays a crucial role in enhancing readability and professionalism. Tools such as Grammarly can assist authors in improving linguistic accuracy and clarity. Proper citation practices and reference management, supported by tools like Mendeley, are also vital to maintain academic integrity and avoid plagiarism. Furthermore, selecting a suitable target journal significantly influences the likelihood of acceptance. Researchers are encouraged to evaluate journal rankings and scopes using platforms such as Scimago Journal Rank and Elsevier Journal Finder. Adherence to ethical standards, including originality, transparency, and compliance with journal guidelines, is mandatory throughout the publication process. Finally, the peer review stage requires careful attention, as authors must respond to reviewers’ comments in a clear, respectful, and evidence-based manner. In conclusion, successful publication in Scopus Q2 journals is achieved through the integration of strong research novelty, structured writing, appropriate journal selection, language proficiency, and effective revision strategies. These combined efforts significantly enhance the probability of acceptance in reputable international journals.